2009
DOI: 10.3141/2135-15
|View full text |Cite
|
Sign up to set email alerts
|

Built Environment or Household Life-Cycle Stages–-Which Explains Sustainable Travel More?

Abstract: Sustainable travel is a goal deserving of research and implementation, but how such a goal can be reached is debated. Fueling this debate are the many different factors involved in individual travel ranging from values and beliefs to the impact of the built environment. The amount of impact that the built environment may have can be clouded by a person's personal preference for a certain lifestyle and different lifecycle stages have different levels of travel. Although low levels of automobile use have been ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 15 publications
(18 reference statements)
2
33
0
Order By: Relevance
“…Wachs (1979) argued that early-stage households behave in a similar fashion to later-stage households that exist today. Sun et al (2012) showed that a companion cohort effect existed for car usage over time, while previous studies (Benekohal et al, 1994;Newbold et al, 2005;Sun et al, 2009) found that different age groups of people have different behaviors with respect to car ownership and usage.…”
Section: Literature Reviewmentioning
confidence: 55%
See 3 more Smart Citations
“…Wachs (1979) argued that early-stage households behave in a similar fashion to later-stage households that exist today. Sun et al (2012) showed that a companion cohort effect existed for car usage over time, while previous studies (Benekohal et al, 1994;Newbold et al, 2005;Sun et al, 2009) found that different age groups of people have different behaviors with respect to car ownership and usage.…”
Section: Literature Reviewmentioning
confidence: 55%
“…Based on research about children's travel in the USA, one might assume that this is the result of chauffeuring, but research in Japan (SBSJ, 2000;Sun et al, 2009) showed that children there mostly travel independently on weekdays, which is Tables 3 and 4 as well. The second reason might be that as individuals enter into family lifecycle stages that stimulate the desire for a larger residence, each successive generation generally locates further from the urban centers leading to longer trip times and potentially greater reliance on cars for transportation.…”
Section: Estimation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their study also suggests that household income has positive impacts on traveling with family members. Households' life-cycle stages and children's attributes, such as the presence of children in households and the age of the youngest child, influence parents' activity-travel patterns significantly (McDonald, 2005;McDonald, 2006;Sun, Waygood, Fukui, & Kitamura, 2009;Tillberg Mattsson, 2002;Waygood, 2011). Multiple studies indicate that children at different ages impose different constraints on joint travel patterns as children's ages increase, the burden of adult chauffeuring and supervision decreases (Ho & Mulley, 2015;Vovsha et al, 2003;Vovsha & Petersen, 2005).…”
Section: Joint Travelmentioning
confidence: 99%